2023
DOI: 10.1002/ijfe.2793
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, economic growth and the role of fiscal policy during normal and stress times: Evidence for 26 EU countries

Abstract: This article empirically explores the finance-growth relationship and the performance of the financial system measured by financial depth, accessibility, and efficiency of both financial sectors, that is, institutions and stock markets.It also examines the role of fiscal policy in conjunction with the performance of financial development during both normal and stress times. The data consists of a panel of 26 European Union countries over the period 1990-2020.The results show that during normal times, the finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Its affects economic growth through competition and technological progress (Hye & Lau 2015). The inclusion of these variables is also justified by past empirical investigations (Asteriou et al 2023;Nyalihama 2022;.…”
Section: Data and Variable Justificationmentioning
confidence: 95%
See 1 more Smart Citation
“…Its affects economic growth through competition and technological progress (Hye & Lau 2015). The inclusion of these variables is also justified by past empirical investigations (Asteriou et al 2023;Nyalihama 2022;.…”
Section: Data and Variable Justificationmentioning
confidence: 95%
“…Nkansa et al (2023) also consider political stability, rule of law, and regulatory quality to magnify the positive effect of financial development on economic growth in SSA countries. Likewise, Asteriou et al (2023) using 26 EU countries affirm the importance of the stock market but found financial institution to be more effective in promoting growth. Similarly, Igbinovia & Igbinovia (2023) found financial development to exert a positive impact on economic growth in the ECOWAS sub-region between 2012 and 2020.…”
Section: Empirical Literaturementioning
confidence: 96%
“…The variables TEMP and CO2 are considered in modelling in their form of first difference, temperature variation and CO2 emissions variation respectively. System GMM (Arellano and Bond, 1991;Blundell and Bond, 1998;Roodman, 2009) was selected as the appropriate dynamic panel technique method for this study because it has the ability to address types of data such as those collected by us, in terms of panel size (21 years and 27 states) and adequately manages heteroscedasticity, serial correlation, cross-sectional dependence and endogeneity, respectively reverse causality problems between variables (Sarafidis and Wansbeek, 2012;Kumar et al, 2022;Asteriou et al, 2023;Gerged et al, 2023). We opted for the Generalized Method of Moments (GMM) over other methods for several key reasons:…”
Section: Methodsmentioning
confidence: 99%
“…Impact of the quarantine regime on the level of investments according to the sector. References (Adnan and Hasan 2021;Ali et al 2022;Asteriou et al 2023;Clark et al 2021;González and Gallizo 2021;Hasnaoui et al 2021;Huynh et al 2021;Kurien ė 2022;Liedtke 2021;Liu et al 2022;Lutfi et al 2022;Nguyen and Vu 2021;Nikolajenko et al 2021;Pileckait ė and Subačien ė 2023;Pourmansouri et al 2022;Rahman et al 2022;Ramachandran et al 2021;Raza et al 2022;Senkus et al 2022;Shabir et al 2023;Simoens and Vander Vennet 2022;S ūdži ūt ė and Jakubavičius 2022;Toth et al 2022;Wulandari et al 2022;Zheng and Zhang 2020;Žinyt ė and Jurkonien ė 2023) are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%